Optimization of alkali pretreatment and enzymatic saccharification of jute (Corchorus olitorius L.) biomass using response surface methodology. (January 2023) - Sharma, Laxmi; Alam, Nurnabi Meherul; Roy, Suman; Satya, Pratik; Kar, Gouranga; Ghosh, Subhojit; Goswami, Tinku; Majumdar, Bijan
Graphical abstract: Highlights: Jute biomass with 66.6% cellulose and 19.4% lignin is suitable bioethanol feedstock. Pretreatment and saccharification was optimized with response surface methodology. Disrupted and loose structure of pretreated biomass revealed better quality. Delignification (80.4%) and saccharification (76.5%) was obtained. Abstract: Reduction of inherent structural recalcitrance and improved saccharification efficiency are two important facets to enhance fermentable sugar yield for bioethanol production from lignocellulosic biomass. This study optimized alkaline pretreatment and saccharification conditions employing response surface methodology to improve saccharification yield of jute ( Corchorus olitorius cv. JROB-2) biomass. The biomass is composed of cellulose (66.6 %), lignin (19.4 %) and hemicellulose (13.1 %). NaOH concentration exhibited significant effect on delignification during pretreatment. The highest delignification (80.42 %) was obtained by pretreatment with 2.47 % NaOH at 55.8 °C for 5.9 h removing 79.8 % lignin and 34.2 % hemicellulose from biomass, thereby increasing cell wall porosity and allowing better accessibility to saccharification enzyme. During saccharification optimization, significant effect was observed for biomass loading, enzyme concentration and temperature. Optimized saccharification condition yielded maximum saccharification (76.48 %) when hydrolysis was performed at 6.9 % biomass loading with enzyme concentration of 49.52 FPU/g substrate at 51.05 °C for 74.46 h.